STRATEGI PENGGUNAAN VIDEO SEBAGAI MEDIA PEMBELAJARAN DI PENDIDIKAN VOKASIONAL: TINJAUAN LITERATUR - Idah Faridah (CV. ADIBA AISHA AMIRA, 2025)
This research aims to present a literature review on strategies for using video as a learning medium in vocational education. Video has become an important part of modern learning, increasing student engagement and understanding. This research will analyze various strategies for using video in the context of vocational education, as well as the benefits and challenges in its application. The method in this research is a literature study that will involve analyzing 20 national journals, 5 international journals, and accredited journals that are relevant to the topic of discussion. The results of this research are expected to provide a deeper understanding of how video can be used eflectively as a learning medium in vocational education.